Germinación de semillas y clave para la identificación de plántulas de seis especies arbóreas nativas de humedales del sureste de México - Zamora-Cornelio, Luis Felipe (2010)
Wetland tree species are of importance for economic and restoration purposes. We describe the germination process and seedling morphology of six arboreal native species typical of Southeastern Mexico: Annona glabra, Ceiba pentandra, Pachira aquatica, Haematoxylum campechianum, Coccoloba barbadensisand Crataeva tapia. A total of 300 seeds per species were planted in a mixture of sand, cocoa plant husk and black soil (1: 1: 1), and maintained in a tree nursery with 30% artificial shade, from February to November of 2007. We carried out the morphological characterization, and elaborated a key to seedlings based on: 1) ger-mination type 2) seedling axis and 3) leaf elements. P. aquatica has cryptocotylar hypogeal germination, the others have phanerocotylar epigeal germination. Germination rates were high (>86%), except for C. barbadensis(69%).